2013
DOI: 10.1111/imb.12052
|View full text |Cite
|
Sign up to set email alerts
|

Silencing ofP‐glycoproteinincreases mortality in temephos‐treatedAedes aegyptilarvae

Abstract: Re-emergence of vector-borne diseases such as dengue and yellow fever, which are both transmitted by the Aedes aegypti mosquito, has been correlated with insecticide resistance. P-glycoproteins (P-gps) are ATP-dependent efflux pumps that are involved in the transport of substrates across membranes. Some of these proteins have been implicated in multidrug resistance (MDR). In this study, we identified a putative P-glycoprotein in the Ae. aegypti database based on its significantly high identity with Anopheles g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
64
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(67 citation statements)
references
References 70 publications
(85 reference statements)
2
64
0
1
Order By: Relevance
“…In mosquitoes, the ABCB2 gene was showed by quantitative PCR to be eightfold up-regulated in larvae of a susceptible strain of Ae. aegypti analysed at 48 h post temephos-treatment [29]. The ABCB4 gene was showed to be over-transcribed by transcriptome and quantitative PCR analyses, in DDT and pyrethroid (permethrin and deltamethrin) resistant Ae.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In mosquitoes, the ABCB2 gene was showed by quantitative PCR to be eightfold up-regulated in larvae of a susceptible strain of Ae. aegypti analysed at 48 h post temephos-treatment [29]. The ABCB4 gene was showed to be over-transcribed by transcriptome and quantitative PCR analyses, in DDT and pyrethroid (permethrin and deltamethrin) resistant Ae.…”
Section: Discussionmentioning
confidence: 99%
“…stephensi , we performed bioassays using a sub-lethal dose of the ABC transporter inhibitor verapamil in association with permethrin. The results obtained using this approach highlight that the combination of insecticides with an ABC-transporter inhibitor can increase the efficacy of the insecticide molecule [18, 29, 55]. In prospect, combined treatments of insecticide plus ABC-transporter inhibitors could be proposed, with the objective of reducing the current dosages of insecticides or to prevent the development of resistance, and reduce environmental pollution [29, 56].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The present study showed an overregulation of P-gp in C. rogercresseyi treated with azamethiphos that was significantly greater than the response obtained in adults treated with deltamethrin, thus demonstrating a strong interaction of P-gp with organophosphates. Likewise, when the expression of P-gp was blocked in A. aegypti via RNAi, an increased susceptibility to the temephos drug was triggered (Figueira-Mansur et al, 2013). On the other hand, an interaction between P-gp and deltamethrin in C. rogercresseyi cannot be ruled out as an increased expression of P-gp was observed with a 2 ppb concentration of deltamethrin.…”
Section: Contigmentioning
confidence: 99%